Mathematical modeling of heat exchange processes for air-inflatable cylindrical collectors - O. A. Smirnova; Y. E. Avetisyan (Advanced Engineering Research)
Introduction. A new type of devices for collecting and accumulating energy – an air-inflatable collector – is considered. As a rule, inflatable collectors are installed permanently which does not imply the orientation of the collector following the solar motion. Due to the low costs of the products in question, it is necessary to offer and investigate the most efficient design. Materials and Methods. A collector consisting of seriesconnected closed cylindrical segments is considered. Cavities of the cylinders are filled with air which maintains the structure constancy. Mathematical modeling of the definition of the airinflatable collector temperature field is performed using the finite element method.Research Results. The temperature field distribution as a function of the direction of solar radiation flow is substantiated experimentally. Mathematical models are considered adequate. The increase in temperature of the heat-absorbing layer with respect to the ambient temperature is from 7 ° to 26.2 ° depending on the part of the collector segment. Discussion and Conclusions. In the course of simulation and experimental studies, it is established that the collector efficiency, apart from solar insolation, is affected by a range of environmental factors: air humidity, wind force, etc. In this case, it is necessary to take into account the device design, as well as the operational and thermophysical characteristics of the materials used. A detailed study of the severity of exposure of external and internal factors on the collector temperature field requires the subsequent development of the software package.